First detection of Eustrongylides excisus (Nematoda: Dioctophymatidae) in big-scale sand smelt (Atherina boyeri) from the lake Massaciuccoli (Northwest Tuscany, Italy): implications for public health and seafood quality. (February 2021) - Guardone, L.; Ricci, E.; Susini, F.; Polsinelli, E.; Guglielmone, G.; Armani, A.
Abstract: Eustrongylides spp. are cosmopolitan parasitic nematodes with several freshwater fish species as intermediate or paratenic hosts, rarely reported as zoonotic agents. This work aims to report, for the first time, the occurrence of this parasite in specimens of big-scale sand smelt ( Atherina boyeri ) caught in the lake Massaciuccoli (Northwest Tuscany, Italy). Totally 3317 specimens of A. boyeri were collected in three different samplings (August–October 2019). Fish were visually examined and then submitted to artificial digestion. Visible parasites were collected and counted after both procedures, then they were identified to genus level by microscopic examination and to species level by molecular analysis of the ITS gene region. Overall, 75 nematodes identified as larval stages of Eustrongylides excisus were found (P: 2.3% 95% CI 1.8–2.8; MA: 0.02; MI: 1), in the viscera and in the muscle. A. boyeri is a highly appreciated fish species in several Italian areas as well as in various Mediterranean countries. Beside an epidemiological interest due to its role in the parasite cycle, the report of E. excisus in the study area arises possible quality and public health issues. Therefore, also considering the method of preparation of A. boyeri and that lately the increasing consumption of raw fish has also targeted freshwater fish species, it is essential to communicate the presence of this hazard and the need of applying appropriate sanitary measures to all FBOs along the supply chain and to consumers. Highlights: Eustrongylides excisus was found in Atherina boyeri from Tuscany for the first time. Molecular characterization of the ITS region allowed specific identification (78). Public health and quality issues may arise.